THE EFFECT OF CAREER DEVELOPMENT AND EMPLOYEE ENGAGEMENT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AT PDAM SURYA SEMBADA CITY OF SURABAYA - Angelina, Noris; Rini, Hesty Prima (UNIVERSITAS PAKUAN, 2025)
The purpose of this study is to understand how career development and employee engagement can have an impact on improving employee performance, with job satisfaction as an intermediary. The object of study in this study is PDAM Surya Sembada which is located in the city of Surabaya. The determination of the research sample was carried out using a non-probability sampling technique with a saturated sampling method, so that the entire population of 87 employees was used as respondents. Data collection was carried out through the distribution of questionnaires to employees. Furthermore, the collected data was analyzed with the help of SmartPLS software, and a series of tests were carried out to ensure the accuracy of the data and test the conjectures in this study. The findings indicate that the career development carried out by the company is able to encourage the improvement of employee performance. Similarly, the active involvement of employees in their workplace will have an impact on improving their performance. Job satisfaction plays an important role as a bridge between career development and employee engagement in improving employee performance. Employees who get clear career development, have a sense of attachment and satisfaction with the company or their job will make their performance improve.